Leaf injury index: A quantitative approach for rapid screening of drought tolerance in citrus rootstocks - MORADE, AMRUT S; SHARMA, R M; DUBEY, A K; S, LEKSHMY; KADAM, D M; AWASTHI, O P; MAHAVER, A K; DEEPAK (The Indian Journal of Agricultural Sciences, 2025)
The present study was carried out during 2019–2021 at ICAR-Indian Agricultural Research Institute, New Delhi to observe leaf injury symptoms and number of functional leaves in nine citrus rootstock genotypes subjected to drought stress. The experiment was laid out in a completely randomized block design (CRBD) with four replications. Qualitative leaf injury symptoms, namely yellow, rolled, scorched, defoliated leaves, and leaf wilting were used as weighted indicators after normalization. A composite weighted indicator-based index, the leaf injury index (LII) was then developed to evaluate the drought tolerance in citrus rootstocks. Citrus genotype RLC-2 exhibited the highest values for yellow (29.75), rolled (22.75), scorched (20.75) leaves, and leaf wilting score (4.50), while Grambhiri showed the highest defoliation count of 16.25. In contrast, X639 had the highest number of functional leaves (79.13) with lowest visible leaf injury in terms of yellow, rolled, scorched, and defoliated leaves, and leaf wilting score. The effectiveness of LII in measuring the drought sensitivity of citrus rootstock genotypes was tested using a heatmap and cluster analysis. Citrus genotype X639 was grouped into a single distinct cluster with the significantly lowest LII (0.250), indicating its drought tolerant nature. The other tested genotypes were classified into three sub-clusters: drought-sensitive (Cleopatra mandarin, RLC-2, RLC-1 and Grambhiri), intermediate drought response (RLC-7 and Troyer citrange), and some degree of drought tolerance (RLC-4 and RLC-5), with their higher, intermediate and lower LII respectively. This composite indicator ideally converts multiple qualitative indicators into a simple, rapid and cost-effective framework for screening citrus germplasm against drought stress.